2016
DOI: 10.1002/pola.28409
|View full text |Cite
|
Sign up to set email alerts
|

Polyimides with side groups: Synthesis and effects of side groups on their properties

Abstract: Polyimides are a class of well‐known high‐performance polymers combined the excellent mechanical, electrical, and thermal properties and widely applied in many high‐tech fields. Traditional polyimides can only be processed in the state of soluble intermediates with a hazardous step of cyclodehydration and elimination of a nonvolatile polar solvent. Therefore, a great effort has been devoted to the development of soluble polyimides that can be processed in the full imidation state. The incorporation of side gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 190 publications
(277 reference statements)
0
58
0
Order By: Relevance
“…However, their industrial application has been limited due to their high cost, high methanol permeability, and low operational temperature. [21][22][23][24] Cross-linking is an efficient and simple method to maintain the water stability of a SPI membrane with a high degree of sulfonation. 12,13 Aromatic polyimide is an exceptional polymer possessing high mechanical properties, excellent thermal dimensional stability, and superior chemical resistance, and it is ideal for PEMFC applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their industrial application has been limited due to their high cost, high methanol permeability, and low operational temperature. [21][22][23][24] Cross-linking is an efficient and simple method to maintain the water stability of a SPI membrane with a high degree of sulfonation. 12,13 Aromatic polyimide is an exceptional polymer possessing high mechanical properties, excellent thermal dimensional stability, and superior chemical resistance, and it is ideal for PEMFC applications.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, in practical use, the water stability of highly sulfonated six-membered-ring SPIs still needs to be improved to meet industrialization standards. [21][22][23][24] Cross-linking is an efficient and simple method to maintain the water stability of a SPI membrane with a high degree of sulfonation. Thus far, several studies on cross-linked SPIs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the chemical modifications in aromatic polyamides are carried out in a systematic way to obtain homopolyamides, block or random co‐polyamides, through varying in the monomer concentrations and evaluating their effects on some properties . Copolymerization approach often allows to control the degree of structural modification to obtain an optimum composition with a balance between the different properties, such as solubility, mechanical properties, thermal resistance, or chemical resistance . In PEBAX copolymers, which containing poly(ethylene oxide) segments and rigid polyamide segments, the gas transport properties are different from their homopolymers; moreover, these copolymers bridge the gap between thermoplastic and rubber behavior .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Copolymerization approach often allows to control the degree of structural modification to obtain an optimum composition with a balance between the different properties, such as solubility, mechanical properties, thermal resistance, or chemical resistance. 15 In PEBAX copolymers, which containing poly(ethylene oxide) segments and rigid polyamide segments, the gas transport properties are different from their homopolymers; moreover, these copolymers bridge the gap between thermoplastic and rubber behavior. 16 Technora, a random copolyamide was obtained copolymerizing terephtalic acid with p-phenylenediamine and 3,4 0 -oxydianiline in a molar ratio 100/ 50/50, this composition was optimum for improved solubility and obtaining excellent physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Fortunately, the introduction of bulky pendant substituents can improve the processability and optical transparency without seriously sacrificing the thermal stability of PIs. [16][17][18][19][20][21] In other words, PIs containing alicyclic moieties as bulky pendant substituents were more stable than those as structural units in main chains. [22][23][24] In addition, our earlier works indicated tert-butyl as ortho-substituent of amino-groups in diamine was greatly enhanced the solubility of corresponding PIs while restrained the formation of CTC to improve the transparency of PI films.…”
mentioning
confidence: 99%